Core summary for IODP Site 386-M0084 - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
List of recovered cores from the above given site on International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. Cores have been acquired by the use of a Giant Piston Coring (GPC) System. The GPC system consists of a set of two coring barrels - a piston corer and a trigger corer. According to IODP core type nomenclature, cores retrieved from the piston corer barrel are labelled by the letter "H" (for hydraulic piston corer) and those from the trigger corer are identified by the core type letter "P" (for push corer). For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023